До становлення курганної археології України: досягнення та проблеми - Отрощенко, В.В.; Болтрик, Ю.В. (Археологія і давня історія України, 2020)
Корифей української археології Дмитро Якович Телегін (1919—2009) доклав чимало зусиль до становлення курганної археології, очоливши дві новобудовні експедиції — Вільнянську (1968—1969) та «Дніпро—Донбас» (1969—1975). Він же, спільно з С. Н. Братченком, зробив великий внесок у розроблення сучасної методики розкопок давніх могил з використанням важкої землерийної техніки. А ще виявив громадянську позицію, захищаючи на засіданні вченої ради ІА АН УРСР молодшого колегу Олександра Михайловича Лєскова (1933—2017), де було поставлено питання щодо звільнення останнього з роботи на початку 1973 р. Відтоді минуло понад 40 літ, коли О. Лєсков на схилку свого життя вирішив пригадати все щодо тих драматичних подій та оцінити свій внесок в археологію. The book of memoirs of our teacher, Professor Alexander Leskov (1933—2017) prompted us to address the topic of the deployment of a wide front of archaeological research in the areas of reclamation construction in the south of Ukraine. Unfortunately, posthumously. It is said that one can say either good or nothing about the departed. Such approach is appropriate in memorial ceremonies or in nostalgic memories of a round date. But «Archaeologist’s notes» was announced in the Preface of the Corresponding Member of the Russian Academy of Sciences A. Ivanchik as «an important document for the historian of Russian science». In this case the document, left to the descendants by the famous scholar, requires meticulous approach by colleagues, especially those who were the witnesses of events which are set forth in the lengthy and not easy to read text. The attention of authors of the paper is focused on the fruitful Ukrainian period of scientific and organizational activity of the famous scholar, his successes and blunders. The events, described in the memoirs, reflect not only his personal dramatic life but also the archeology of the Ukraine, the acquisition of its independence in the conditions of inevitable political crisis. O. Leskov’s expeditions like a powerful bulldozer have passed through the kurgans of steppe Ukraine plowing many artifacts to the surface. The wavering between the glitter of Scythian gold and the urgent problems of the Late Bronze Age left the author of the «Memoirs» in the grip of scientific stereotypes and ideas of the 1970s. Archaeologists in Ukraine have switched to a more informative method of excavating of mounds with several parallel balks but this has already happened without the detonator of the kurgan boom. After all, the science has never been for O. Leskov above all but was only a tool for achieving specific life positions. Sometimes it seems that the scholar in him always competed with the manager, but it didn’t occur to the author of «Memoirs» to choose between those entities.